Enhancing Online Learning: Integrating Social Interaction Dimension into The Felder Silverman Learning Style Model - Mohd Zainuri Bin Saringat; Supangat Supangat (Information Systems - Universitas Pesantren Tinggi Darul Ulum, 2026)
This study aims to investigate the impact of enhancing Felder Silverman Learning Style Model (FSLSM) by integrating social interaction on student learning per-formance. A mixed methods was performed to analyze the usage to 400 data col-lected in Indonesia. The findings show that social interaction play significant roles on the enhancing FSLSM. Interestingly, the social interaction dimension that are not considered in the FSLSM, does act as the influencer. This study high-lights the combination of FSLSM and social interaction dimension can create a comprehensive description of students learning styles which has an impact on student’s learning performance which increased by 4.5%. The study suggested that online learning platform should have features that can retain comprehensive and personalized learning experiences, which may create a better online learning platform and positively affect users’ learning performance.